Can someone please help me with this? I just went back to school and my brain isn't functioning correctly.
lol, thank you! :-)
Let x equal the number of miles she ran the 1st day.
Let (x - 6) equal the number of miles she ran the 2nd day.
Let (x + 2) equal the number of miles she ran the 3rd day.
Solve for x:
x + (x - 6) + (x + 2) = 32
3x - 4 = 32
3x = 36
x = 12 miles
12 miles the first day.
6 miles the second day.
14 miles the third day.
** Always check your work **
12 + 6 + 14 = 32 miles.
Good luck in your studies,
~ Mitch ~
I corrected my error, as I had misread the question.
Seems like my brain isn't functioning correctly either ^-^.
day one=a day 2 =b day 3 = c
x stands for second day
(6+x) + x + (2 + x) = 32
since she ran 6 less than first day on her second day, it is the same as running six more on first day than second day..same with the third day
solve the rest yourself
I am pretty sure Mitch's answer is wrong
she ran 14 miles, lol sry i was born a little slow 0.o
EDIT: Sorry to say mitch, but .33 + .33 + .33 is equal to .99 0.o
She ran 14 miles on the first day, 8 on the second day, and 10 on the third day.
X is the miles run on the first day
X-6 is the miles run on the second day (this is straight from the problem)
X-4 is the miles run on the third day (If she ran 2 miles less on the second day than the third, she ran 4 miles less on this day than the first)
Lets add up the miles
X + (X-6) + (X-4) = 32 ==>
3X - 10 = 32 ==>
3X = 42
X = 14
Alisha ran 14 miles on the first day.
This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.
More Questions & Answers...